AGP/EBP(LAP) expressed in rat hepatoma cells interacts with multiple promoter sites and is necessary for maximal glucocorticoid induction of the rat alpha-1 acid glycoprotein gene. - Williams, P (1991)
Transcription of the rat alpha 1-acid glycoprotein (AGP) gene is induced by glucocorticoids. In addition to the glucocorticoid response element which maps to bases -120 to -107, sequences located between bases -106 to -42 have been shown to be necessary for hormone induction. We have previously identified multiple sites of C/EBP interaction with the AGP promoter in the region -106 to -64. In this study, we purify and identify a C/EBP family member, AGP/EBP(LAP), present in the rat hepatoma cell line HTC (JZ.1) which also binds to the C/EBP recognition sites in this region. Mutations in the recognition sites that prevent binding are analyzed, and the results suggest a positive as well as a possible inhibitory role for AGP/EBP(LAP) in the glucocorticoid induction of the gene in HTC (JZ.1) cells.